Saturday

March 28, 2015

March 28, 2015

Posted by **Ashley** on Saturday, April 14, 2007 at 1:57pm.

tanx(cos2x) = sin2x - tanx

Left Side = (sinx/cosx)(2cos^2 x -1)

=sinx(2cos^2 x - 1)/cosx

Right Side = 2sinx cosx - sinx/cosx

=(2sinxcos^2 x - sinx)/cosx

=sinx(2cos^2 x -1)/cosx

= L.S.

Q.E.D.

**Answer this Question**

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Math - Im really struggling with these proving identities problems can somebody ...

maths - trigonometry - I've asked about this same question before, and someone ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Trigonometry - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...